Investigating the impact of search results for fever, headache, cough, diarrhea, and nausea on the incidence of COVID-19 in India using Google Trends - Verma, Renuka; Ramphul, Kamleshun; Kumar, Nomesh; Lohana, Petras (Acta Biomedica Atenei Parmensis, 2021)
-